Effectiveness of the Dual Approach Program to promote sexual abstinence in Thai early female adolescents and improve parent-daughter sexual communication - Kultida Hattakitpanichakul; Rutja Phuphaibul; Srisamorn Phumonsakul; Chukiat Viwatwongkasem (Journal of Health Research, 2019)
Purpose - The purpose of this paper is to examine the effectiveness of abstinence-based sexual education programs delivered in parallel to Thai parents and their early adolescent daughters to promote sexual abstinence and improve communication regarding sexual topics between them and their parents. Design/methodology/approach - A quasi-experimental design included groups of parent/daughter dyads; Group 1 (controls) (n=40), Group 2 Adolescent Program (n=40) and Group 3 Adolescent Parent Program (APP) (n=42). Outcome measures included parent–adolescent communications and adolescents’ sexual abstinence cognitions and intent to abstain from sexual behaviors, measured at five and nine weeks post-programs. Findings - Generalized estimating equation analyses indicated that the dual program (APP) was more effective in increasing parental communication with their daughters compared with Group 1 (p-value<0.05) and only the daughters in the APP program reported more positive subjective norms, sense of perceived behavioral control and intent to abstain than did Group 1 (p-value<0.05). Originality/value - The overarching goal of supporting the development of family environments where female adolescents are able to talk about sexuality is essential for adolescent sexual health promotion. The data provide further evidence that a dual program with simultaneous parent and female adolescent interactive activities over three sessions is superior compared with programs that target either the parents or the adolescents only. Hence, further replication with more parent–daughter dyads and then within more diverse cultures and populations is warranted. Developing and testing a similarly structured program for parents and sons is also required.